Capacity to Elicit Cytotoxic CD8 T Cell Activity Against Mycobacterium avium subsp. paratuberculosis Is Retained in a Vaccine Candidate 35 kDa Peptide Modified for Expression in Mammalian Cells - Franceschi, Valentina; Mahmoud, Asmaa H.; Abdellrazeq, Gaber S.; Tebaldi, Giulia; Macchi, Francesca; Russo, Luca; Fry, Lindsay M.; Elnaggar, Mahmoud M.; Bannantine, John P.; Park, Kun-Taek; Hulubei, Victoria; Cavirani, Sandro; et al. (Frontiers in Immunology, 2019)
Studies focused on development of an attenuated vaccine against Mycobacterium avium subsp. paratuberculosis (Map), the causative agent of paratuberculosis (Ptb) in cattle and other species, revealed deletion of relA, a global gene regulator, abrogates the ability of Map to establish a persistent infection. In the absence of relA, cattle develop CD8 cytotoxic T cells (CTL) with the ability to kill intracellular bacteria. Analysis of the recall response to a relA mutant, Map/ΔrelA, with cells from a vaccinated steer demonstrated a 35 kDa membrane peptide (MMP) is one of the targets of the response. This observation suggested it might be possible to develop a peptide-based vaccine. As reported here, the gene encoding the hypothetical MMP ORF, MAP2121c, was modified for expression in mammalian cells as a first step in developing an expression cassette for incorporation into a mammalian expression vector. The modified sequence of MMP, tPA-MMP, was mutated to generate two additional sequences for the study, one with substitutions to replace 5 potential residues that could be glycosylated, tPA-MMP-5mut, and one with substitutions to replace the first two potential residues that could be glycosylated, tPA-MMP-2mut. The sequences were placed in an expression cassette to produce peptides for analysis. An Ex vivo platform was used with flow cytometry and a bacterium viability assay to determine if modifications in the gene encoding MMP for expression in mammalian cells altered its capacity to elicit development of CD8 CTL, essential for its use in a peptide based vaccine. Monocyte depleted PBMC (mdPBMC) were stimulated with antigen presenting cells (APC) pulsed with different MMP constructs. CD4 and CD8 T cells proliferated in response to stimulation with MMP (control) expressed in E. coli (eMMP), tPA-MMP, and tPA-MMP-2mut. CD8 T cells retained the capacity to kill intracellular bacteria. The tPA-MMP-5mut failed to elicit a proliferative response and was not included in further studies. The data show the expression cassettes containing MMP and MMP-2mut can be used to screen and select a mammalian expression vector for the development of an efficacious peptide-based vaccine against Ptb.